A culturally embracing economic model for sustainable regional development - Chitsika, Ruben, author; Geroy, Gary, advisor; Edgeman, Richard L., committee member; Banning, James H., committee member; Fan, Liang-Shing, committee member (Colorado State University. Libraries, 2002)
The increased globalization of the modem world prompts questions about the role of the depth and persistence of cultural differences: culture as an influence on developing and sustaining performance excellence processes and cultural durability in the face of economic change and cross-cultural political-economic contact. This study was designed to develop a culturally embracing economic model for sustainable regional development. The study uses a meta-theory and meta-analysis multidisciplinary-grounded theory research design within the qualitative research methodology to explore and identify factors, which if present, constitute and optimize a successful culturally embracing economic model for sustainable regional development. A culturally embracing economic model for sustainable regional development has emerged. The model was validated by a group of international experts in anthropology, sociology, business, regional economic development, political science and sustainable development. Its strength lies in it being a dynamics model, which affords it the flexibility and adaptability to successfully function in organizations of different types and sizes. This study encourages emerging regional economies to promote the importance of human capital development and deployment, create practices, processes, and systems that leverage human capital to create value for the stakeholders, and explore the ecological base as a necessity for sustainable development and promoting the view that it is very difficult to separate communities from their natural environment and its ability to sustain them. There is need to put in place systems that nurture ongoing relationships among actors, whom the local and regional interest groups are part of, for them to realize sustainable development for the benefit of all stakeholders. This study views culture as an interactive dynamic in economic planning for sustainable development and focuses on the role of culture and its interaction with other systems, which have been more traditional basis for looking at development models. For organizations, nation-states and region-states that plan for sustainable development, this study provides a new paradigm, one that is active and culture-centered, and cuts across disciplines.
Keywords: social structure; urban planning; area planning and development; culture; studies; cooperation; regionalism